Effects of short-term exposure to elevated atmospheric CO2 on yield, nutritional profile, genetic regulatory pathways, and rhizosphere microbial community of common bean (Phaseolus vulgaris) - Duarte, Rafael D. C.; Nunes da Silva, Marta; Fortunato, Gianuario; Quirós-Vargas, Juan; Muller, Onno; Manaia, Célia M.; Vasconcelos, Marta W. (Plant and soil, 2025)
Aim Legumes are vital to agroecosystems and human nutrition, yet climate change is compromising their nutritional value. This study aims to assess how a one-month exposure to elevated CO 2 (eCO 2 ) impacts biomass yield, mineral profile, gene expression, and the soil microbiome of common bean plants ( Phaseolus vulgaris L.). Methods Phaseolus vulgaris L. was grown in field conditions under ambient CO 2 (control, aCO 2 , 400 ppm) or eCO 2 (600 pm) from the start of pod filling until plant maturity and analyzed for several morphophysiological and nutritional parameters. Results Compared with aCO 2 , eCO 2 exposure significantly increased plant and grain biomass, with fluctuations in mineral accumulation. Notably, it decreased grain iron and zinc concentrations, two essential microelements related to food security, by 59% and 49%, respectively. Additionally, grain phenolic content decreased by up to 41%. Genes involved in mineral uptake (such as FER1 , ZIP1 , and ZIP16 ), plant response to stress ( TCR1 , TCR2 , and HLH54 ) and symbiosis with soil microorganisms ( NRMAP7 and RAM2 ) seemed to regulate effects. Microbiome analysis supported these findings, with an increase in the relative abundance of Pseudomonadota by 10%, suggesting eCO 2 -induced alterations in microbial community structure. Conclusions This research demonstrates how eCO 2 impacts the nutritional quality of common beans regarding micronutrients and phenolic content, while also affecting soil microbiome composition. Highlighting the value of shorter term eCO 2 treatments, the findings provide early insights into immediate plant responses. This underscores the need for crop improvement strategies to address nutrient deficiencies that may arise under future eCO 2 conditions.